CHANNELIZATION STRATEGIES OF RADICALISM AMONG MUSLIM UNIVERSITY STUDENTS IN INDONESIA (State Islamic University (UIN) of Sunan Ampel Surabaya, 2020)
This article examines the channelization of radicalism by fundamentalist-religious organizations among Muslim university students in Indonesia. The data are taken from 700 Muslim students’ respondents in seven Indonesian universities. This study finds that the channelization of radical-religious ideology in Indonesia takes place via new media with three layers of channels: open-public channel, restricted-public channel, and private channel. The first channel, which is relatively public and overt media platforms, is used to communicate and launch their messages, as well as to expand their ideological propaganda. The second channel, which includes some public but relatively closed media platforms, is used by radical-religious organizations in Indonesia to recruit their new members. By the third channel, a more closed and private media platform becomes the final channel to select new cadres. This research finding is expected to be a complementary reference for the de-radicalization processes that are disseminated via new media to young Muslims and university students in Indonesia.